KARAKTERISASI MUTU TEH HITAM METODE CTC (Crushing, Tearing and Curling): Characterization of Black tea Quality in CTC (Crushing, Tearing and Curling) Method at PTPN XII District Bantaran Region Sirah Kencong - Nur Sriwijayanti; Elfi Anis Saati; Sri Winarsih (Pro Food, 2021)
Abstract This study aims to test the quality of black tea using the cup test method and to test the antioxidant activity of black tea using the DPPH method. The method used in this research is the experimental method. The data obtained from the results of this study are displayed in the form of tables, pictures and discussed in a quantitative descriptive manner. The results showed that CTC black tea had an appearance quality rating of medium/moderate (Fair made), the quality of the brewed water (liquor) was of medium/moderate quality (Fair good), and the quality of the pulp (infused leaf). ) is at best medium quality. The antioxidant activity, starting from the highest, was BMC (Broken Mix CTC) with  of 38,187 ppm, D2 (Dust 2) with I of 38,525 ppm, and PF1 (Pekoe Fanning) with  of 54,907 ppm.   Abstrak Penelitian ini bertujuan untuk menganalisis mutu teh hitam dengan metode cup test dan menganalisis aktivitas antioksidan pada teh hitam dengan metode DPPH. Metode yang digunakan pada penelitian ini adalah metode eksperimental. Data yang diperoleh dari hasil penelitian ini ditampilkan dalam bentuk Tabel, gambar dan dibahas secara deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa Teh hitam CTC memiliki penilaian kualitas kenampakan sifat luar (appearance) berada pada kualitas medium/sedang (Fair made), kualitas air seduhan (liquor) berada pada kualitas medium/sedang (Fair good), dan kualitas ampas (infused leaf) berada pada kualitas best medium. Aktivitas antioksidan secara berturut-turut mulai dari yang tertinggi adalah BMC (Broken Mix CTC) dangan  38,187 ppm, D2 (Dust 2) dangan  38,525 ppm, dan PF1 (Pekoe Fanning) dengan  54,907 ppm.